PENGARUH LATIHAN SINGLE - DOUBLE LEG HOP DENGAN BERBEBAN TERHADAP KECEPATAN TENDANGAN DOLLYO CHAGI PADA PESERTA EKSTRAKURIKULER TAEKWONDO DI SMA NEGERI 1 TUMPANG - Anggun Setyaningrum; Ari Wibowo Kurniawan (Cahaya Ilmu Bangsa Institute, 2024)
Basic kicking techniquesdollyo chagi which is mastered by extracurricular taekwondo students at SMA Negeri 1 Tumpang is still very lacking, because the results of kick test observations dollyo chagi of extracurricular participants at SMA Negeri 1 Tumpang in the excellent and good categories 0.00%, in the fair category 23.3% from 7 participants, in the poor category 40% from 12 participants, and 36.7% from 11 participants. Based on the results of observations of extracurricular taekwondo participants at SMA Negeri 1 Tumpang they are still not optimal in kicking.dollyo chagi. This research was conducted to examine the influence that single hop, resistance band and double hop exercises have on kicking ability Dollyo chagi for students who take part in extra taekwondo activities at SMAN 1 Tumpang. One Group Pretest-Posttest Design is the procedure used in the experiment. Thirty people participated in the study. The t test was used to evaluate data from the pre- and post-test. The t table value of 1.697 and the calculated t-value of 16.685 are displayed in the test results. The speed of Dollyo chagi's kicking ability was significantly influenced by single-leg hopping, two-leg hopping, and resistance training with bands, as shown by the fact that the t-count value (16.685) was greater than the T-table value. (1,697)